Prevalence and Characterization of Listeria Species in Domestic and Industrial Cheeses of Isfahan Region - M Zamani-Zadeh; M Sheikh-Zeinoddin; S Soleimanian-Zad (Tehran University of Medical Sciences, 2011)
Background: Listeria monocytogenes is of major concern to the food industry in general and the dairy industry in particular. Little is known about incidence of this pathogenic bacterium in dairy products in Iran. Methods: A survey was made from 23 September 2006 to 22 June 2007 for Listeria species in ninety samples of traditional and industrial cheeses, in milk and surface where the cheeses were manufactured from unpasteurized raw milk in the province of Isfahan (Iran). Results: Listeria murrayi, L. grayi and L. ivanovii, were detected in nine traditional cheeses and one raw milk sample. None of the different Listeria species were isolated from the industrial cheeses and their environment. Conclusion: There are almost good hygienic conditions in domestic cheese manufacturing farmhouses in Isfahan area, but we should try to improve hygienic levels until we have none of the Listeria spp. in our samples.